Development, adoption and commercialization of GM crops: A needed commodity in Nigeria - Alpha, Kargbo; Edrissa, Jawo; Abubakar Sadiq, Abubakar; Moses Edache Entonu, Joseph Yahaya; Jalamang, Camara (African Journal of Biological Sciences, 2020)
Food has been recognized globally as a necessity of life and organization such as World Health Organization (WHO) have made attempts at addressing the global food scarcity crisis. One of the attempts is the introduction of Genetically Modified crops (GM crops). Agricultural productivity is low in Nigeria due to reliance on rainfall and other related factors like poor agronomic practices and crop losses from pest and disease. The benefits of GM crops include increase or improved yield, adoptability to specific abiotic and biotic stresses such as drought, pest and disease among others. Nigeria as a nation is slow in adopting GM crops due to the political debate and public opinion and concerns over public health and safety. The Nigeria National Assembly and Nigerian Academy of Science (NAS) has since declared that GM crop is safe for consumption. However, the commercialization of GM crops in Nigeria still remains to be the challenged. There is need to convince the population on the safety of GM crops based on evidence of success stories of empirical studies for the formulation of regulations and policy guidelines that will promote the development, adoption and commercialization of GM crops for food sufficiency and sustainable development.
Keywords: GM crops, Nigeria, Herbicide, Tolerance, Resistance, Fortification, Commercialization